Gpr37 modulates the severity of inflammation-induced GI dysmotility by regulating enteric reactive gliosis - Keiramarie Robertson; Oliver Hahn; Adarsh Tantry; Beatriz G. Robinson; Arwa T. Faruk; Mathangi Janakiraman; Hong Namkoong; Kwangkon Kim; Jiayu Ye; Estelle Spear Bishop; Randy A. Hall; Tony Wyss-Coray; et al. (iScience)
Summary: The enteric nervous system (ENS) is contained within two layers of the gut wall and is made up of neurons and enteric glial cells (EGCs) that regulate gastrointestinal (GI) function. EGCs in both inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) change in response to inflammation, referred to as reactive gliosis. Whether EGCs restricted to a specific layer or region within the GI tract alone can influence intestinal immune response is unknown. Using bulk RNA-sequencing and in situ hybridization, we identify G-protein coupled receptor Gpr37, as a gene expressed in EGCs of the myenteric plexus, one of the two layers of the ENS. We show that Gpr37 contributes to key components of LPS-induced reactive gliosis including activation of NF-kB and IFN-y signaling and response genes, lymphocyte recruitment, and inflammation-induced GI dysmotility. Targeting Gpr37 presents a potential avenue for modifying inflammatory processes in the ENS.